Pengaruh Kualitas Layanan Akademik dan Birokrasi terhadap Kepuasan Mahasiswa - Sufiyyah, Arrafiatus (Jurnal Ilmiah Aset, 2011)
A better education is a society need that should be considered by institution of education. College should pay attention to the students involving the quality Bureaucracy and Academic service related to students’ satisfaction. The case needs a research in exploring clear information. This research applies quantitative study in the form of correlation research. The population of the research is all the economic faculty students of Unnes, which involves 1850 students with sample 200 student. This research used proportional random sampling. The conclusion of this study, the researcher found that there is correlation about the quality of bureaucracy and academic service to the students’ satisfaction. The suggestion of this research is (1) All academic servers need to keep the better work which has been applied in the quality bureaucracy and Academic service, (2) The economic faculty should improve the quality academic bureaucracy service in order to create better perception of students.